2003
DOI: 10.1002/dvdy.10380
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of the hyoid cartilage depends upon signals arising from the ventral foregut endoderm

Abstract: Hyoid bone is a part of the visceral skeleton which arises from both Hox-expressing (Hox؉) and Hox-nonexpressing (Hox-) cephalic neural crest cells. In a previous work, we have demonstrated that the Hox-neural crest domain behaves as a naïve entity to which the ventral foregut endoderm confers patterning cues to specify the shape and orientation of the nasal and mandibular skeleton. By using ablation and grafting approaches, we have extended our study to the formation of the hyoid bone and tested the patternin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
1
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 21 publications
3
90
1
1
Order By: Relevance
“…During the development of the first branchial arch, pharyngeal endoderm is thought to prepattern the orofacial epithelium, which in turn will provide instructive signals to pattern the CNC-derived mesenchyme (Haworth et al, 2004). In zebrafish studies, fibroblast growth factor (FGF) signaling has been shown to be critical for the development of pharyngeal endoderm itself and for the mediation of the endoderm to regulate facial skeletal morphogenesis (Ruhin et al, 2003;Crump et al, 2004;Helms et al, 2005). On the other hand, a recent study has shown that pharyngeal endoderm is not critical for the normal development of the upper and lower face.…”
Section: The Pharyngeal Endodermmentioning
confidence: 99%
“…During the development of the first branchial arch, pharyngeal endoderm is thought to prepattern the orofacial epithelium, which in turn will provide instructive signals to pattern the CNC-derived mesenchyme (Haworth et al, 2004). In zebrafish studies, fibroblast growth factor (FGF) signaling has been shown to be critical for the development of pharyngeal endoderm itself and for the mediation of the endoderm to regulate facial skeletal morphogenesis (Ruhin et al, 2003;Crump et al, 2004;Helms et al, 2005). On the other hand, a recent study has shown that pharyngeal endoderm is not critical for the normal development of the upper and lower face.…”
Section: The Pharyngeal Endodermmentioning
confidence: 99%
“…Whereas CNCCs give rise to most chondrocranial and dermatocranial elements of the jaws (Clouthier et al, 1998;Couly et al, 2002;Depew and Simpson, 2006;Kontges and Lumsden, 1996;Ruhin et al, 2003), they do not possess, before migration, the topographic information needed to carry out the jaw morphogenesis (Couly et al, 1993). Surgical removal and grafting of small territories of the foregut endoderm at different developmental stages has shown that this epithelium provides to CNCCs part of the topographic information needed to form jaw structures (Couly et al, 1993;Kontges and Lumsden, 1996;Kurihara et al, 1994;Le Douarin and Dupin, 2003;Noden and Trainor, 2005;Trainor and Tam, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It was believed that the pharyngeal arches obtain their identity from neural crest cells that migrate in segmental streams from the hindbrain into the arches . However, several recent studies have shown that the pharyngeal endoderm plays a much more important role in pharyngeal arch development than previously anticipated (Veitch et al, 1999;Piotrowski and Nusslein-Volhard, 2000) and patterns neural crest cells along the anteriorposterior (a/p) axis (Couly et al, 2002;Ruhin et al, 2003). Studies of zebrafish mutants, Xenopus, and knockout mice have significantly contributed to our understanding of how the endodermal germ layer is initially formed (Alexander and Stainier, 1999;Gritsman et al, 1999;Yasuo and Lemaire, 1999).…”
Section: Introductionmentioning
confidence: 99%